Online Brazilian Journal of Nursing for a professional practice based on evidence - Cruz, Isabel (Online Brazilian Journal of Nursing, 2005)
Someone said that the literature is an important aspect of a profession. We agree, but now we would like to affirm the so important as the literature is the use of it to develop the professional practice and to promote human wellness.The OBJN is indexed by almost all scientific databases. It is good for us, but we are not sure that we are changing developing and empowering the nursing profession.The new challenge to the OBJN is to be a reference for the bedside or community nurse. The OBJN wants to give scientific support to any kind of nursing care.